PENGARUH PENYULUHANASI EKSKLUSIF TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL DIKELURAHAN ALUR DUA KECAMATAN SEI LEPAN KABUPATEN LANGKAT - Ika Purnama Sari Purba; Etti Sudaryati; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Nutritional status is closely related to the high rate of morbidity and mortality of infant/toddlers, Exclusive breastfeeding is one effort to reduce morbidity and mortality in infants/toddler.One of the causes of the low coverage of exclusive breastfeeding is the lack of maternal health support in terms of counseling to breastfeed babies. This study aims to determine the effect of Exclusive breastfeeding education on knowledge and attitude of pregnant women in Kelurahan Alur Dua Kecamatan Sei Lepan Kabupaten Langkat. This type of research is quasi experimental with one group pre- and post-test design. The population is all 42 and 42 trimester pregnant women. Sampling technique using total sampling technique, Exclusive breastfeeding effect on mother's knowledge and attitude was analyzed by t-dependent test at 95% confidence level. The results showed that the average value of mother's knowledge before giving Exclusive breast feeding was 7.71 and after being given Exclusive breastfeeding counseling of 12,69, the mean of attitude attitude of mother before giving exclusive breast feeding equal to 38,62 and after giving breast feeding Exclusivity of 54.02, this shows that there is a significant increase (p = 0,000) of knowledge and attitude of mother in giving exclusive breastfeeding between before and after being given Exclusive breastfeeding counseling. It is suggested to Langkat District Health Office for exclusive breastfeeding to mother hami as one of the tools to increase coverage of breastfeeding mother in infants / toddlers and health workers to further improve the quality of health services in providing education. Keywords : Exclusive breastfeeding education, knowledge, attitude, pregnant.